Impact of critical illness news on the family: hermeneutic phenomenological study - Mendes, Anabela Pereira (2021)
OBJECTIVE: Understand the impact of critical-illness news on the experience of family members at an Intensive Care Unit. METHOD: Phenomenological approach according to Van Manen's method. Open interviews were held with 21 family members. From analysis and interpretation of the data, three essential themes were identified: the unexpected; the pronouncement of death; and the impact on self-caring within the family. The study complied with the ethical principles inherent to research involving humans. RESULTS: The unexpected news and death of the sick person influence the well-being and self-care of family members, affecting their ability for analysis and decision making. It was observed that the family experiences the news with suffering, mainly due to the anticipation arising from the events. FINAL CONSIDERATIONS: The humanity of nurses was revealed in response to the needs of the family. In view of the requirements for information, it was verified that the information transmitted allowed them to become aware of themselves, to become empowered in their daily lives and to alleviate the emotional burden experienced.